2020
DOI: 10.1097/gme.0000000000001573
|View full text |Cite
|
Sign up to set email alerts
|

Mediatory role of abdominal obesity in the association of early menopause with diabetes among middle-aged and older Chinese women

Abstract: Objective: The aim of this study was to assess the association of early menopause with diabetes and the mediating effect of abdominal obesity. Methods: This cross-sectional study was conducted among 5,693 participants. The data from the second follow-up (2015) of the China Health and Retirement Longitudinal Study were used. Participants self-reported their age at menopause and were divided into three age groups (<45, 45-54, and >54 years) accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
3
0
1
Order By: Relevance
“…21 However, other studies have shown that the mediating effect of abdominal obesity has no statistical significance, indicating that early age at menopause may independently affect the risk of diabetes. 40 After interaction analysis, our results can confirm the later study that obesity or abdominal obesity has little effect on the relationship. Studies have found that earlier age at menopause is at higher risk of hypertension, 41 and menopause status is associated with dyslipidemia.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…21 However, other studies have shown that the mediating effect of abdominal obesity has no statistical significance, indicating that early age at menopause may independently affect the risk of diabetes. 40 After interaction analysis, our results can confirm the later study that obesity or abdominal obesity has little effect on the relationship. Studies have found that earlier age at menopause is at higher risk of hypertension, 41 and menopause status is associated with dyslipidemia.…”
Section: Discussionsupporting
confidence: 80%
“…A prospective study found that women with later age at menopause who were not obese, and women with earlier age at menopause who were obese were more likely to develop diabetes 21 . However, other studies have shown that the mediating effect of abdominal obesity has no statistical significance, indicating that early age at menopause may independently affect the risk of diabetes 40 . After interaction analysis, our results can confirm the later study that obesity or abdominal obesity has little effect on the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although general and abdominal obesity are both known high-risk factors for T2DM, this study found that a later age at menopause was only associated with total body fat. A recent Chinese study also showed that WC comprised a small percentage and had no statistically significant mediating effect on the association between age at menopause and T2DM 21 . Our study suggested that as Asians are generally leaner than other races, general obesity is more strongly associated with estradiol levels than abdominal obesity in the development of hyperglycemia.…”
Section: Discussionsupporting
confidence: 53%
“…A recent Chinese study also showed that WC comprised a small percentage and had no statistically significant mediating effect on the association between age at menopause and T2DM. 21 Our study suggested that as Asians are generally leaner than other races, general obesity is more strongly associated with estradiol levels than abdominal obesity in the development of hyperglycemia. Prolonged estradiol accumulation may also contribute to hyperglycemia through inflammatory markers.…”
Section: Discussionmentioning
confidence: 59%
“…Общая жировая масса у женщин, как правило, на 10-15% больше, чем у мужчин, на протяжении всей жизни с преобладанием жировой ткани в области бедер. Висцеральное ожирение у женщин развивается в период менопаузального перехода и в постменопаузе [13,14].…”
Section: метаболические нарушенияunclassified